Eğitimci Gözüyle Tasarımda Yaratıcılık Söylemi - Apaydın, Banu (The Turkish Online Journal of Design Art and Communication, 2015)
People's life experiences, by feelings, thoughts and imagination are changed the perception of reformatting existing trends and make the search for solutions to problems where querying the environment has been continued from the past to present. This action can be described as design is the continual changes throughout history and is a result of the world order. Therefore, various methods have been developed in order to reach a correct conclusion and designing action, these methods as theory and practice are tested and has been developed many educational model. Methods that are common concept of such training models; It is to promote and develop creativity. Between 11-Apr- June 13, 2013 at Salt Galata, Faculty of Fine Arts of Marmara University, 6. Within the International Student Triennial "Connecting The Dots / Points My Combining" themed "Point Detail: selective perception" was conducted a workshop titled. A method of how to service the design action with said the workshop aims to theoretically what they learned during the training of a designer considering developing methods for creativity in design and implementation work is to increase the awareness of students with the proposal. The process of design through the eyes of educators such discourse is a discourse of creative work and outcomes.
Keywords: Tasarım; Yaratıcılık; Tasarımda Yaratıcılık; Eğitimci; Algı; Duygu; Design; Creativity; Creative Design; Trainer; Perception; Feelings; Thoughts